Asthma: diagnosis and management in adults. (May 2020) - Cheung Wong, Ernie Hoi; Farne, Hugo Andres
Abstract: Asthma is a common respiratory disorder characterized by chronic airway inflammation and airway hyperresponsiveness. It typically presents with a constellation of symptoms including wheeze, shortness of breath, chest tightness and cough, varying in intensity over time. It is a heterogeneous disease with distinct clinical and molecular phenotypes based on clinical, inflammatory cell and cytokine profiles. Historically, diagnosis has been clinical but misdiagnosis is common, leading to a growing emphasis on objective evidence of variable airway obstruction and/or airway hyperresponsiveness. Management aims to minimize current symptoms and prevent future deterioration, in particular acute exacerbations. Pharmacological treatment is predominantly inhaled therapy (corticosteroid, β-adrenoceptor agonist), prescribed in a stepwise fashion in accordance with disease severity. Non-pharmacological management, principally patient education (but also smoking cessation and allergen avoidance if applicable), plays an equally important role. Although most asthma sufferers achieve stability with inhaled treatment, a minority remain symptomatic despite maximal therapy. Monoclonal antibody therapy is effective for some but not all patients with severe asthma, reflecting disease heterogeneity. Current research therefore focuses on the accurate identification of disease phenotype and potential biomarkers for appropriate targeted therapy.